(untitled) (Nóema, 2014)
This text intends to propose a theoretical reflection on the path proposed by Salomon Maimon and Emmanuel Levinas, inspired by the philosophical aporie of the dialogue Parmenides of Plato on the theme of exaìphnes. Certainly both in the reflection of Levinas and in the reflection of Maimon acts a strongly Jewish force, that inspire our themes: Maimon for the complete resolution of the empirical in the intellect can take place only in the promised land of the infinite, for Levinas, the chiasm between the absolutely Other, which manifests itself escaping at the same time in the face of the other calls us continually to make exodus from ourselves. In the concrete, in that, which has no place, in the break, in the absence, in the discontinuity und in the highly contingent there is the element, that is the true transcendental mediation-element that binds reality, not in the categories of the intellect that provide us only a reality, that is valid for the our perception and objective representation or for a posthumous, fictitious facts. As tertium non datur between these two positions - the infinite intellect of Maimon und the perennial exodus from themselves in Lévinas – we intend to take an absent place of the xynòn or of the absent with (cum), that combines with a paradoxical blending the absolute nominalism of Hume with the world of Plato’s ideas: the place of a absurd, absent homeland.